A Pilot Randomised Controlled Trial Examining the Benefit of a Neutropenic Diet for Children Undergoing Cancer Treatment. (25th July 2022) - Gupta, Aditya; Gupta, Aditya Kumar; Meena, Jagdish Prasad; Khan, Maroof Ahmad; Agarwala, Anuja; Seth, Rachna
Abstract: Neutropenic diet(ND) has been hypothesized to decrease the rate of febrile neutropenia(FN) occurring post-chemotherapy for pediatric cancers. Despite widespread use, it has not shown to be of benefit by randomized controlled trials(RCT) in western countries. No RCT has been conducted in India/LMIC to evaluate its efficacy against the standard Indian diet. Forty-two(42) children, aged 3-14 y, with cancer, scheduled to receive strongly myelosuppressive chemotherapy were randomized to receive either neutropenic diet( n = 21) or standard Indian diet( n = 21) for one chemotherapeutic cycle. FN rate was recorded as the primary outcome while the focus of infection, antibiotic length, the requirement for hospital admission, adherence to diet were the secondary outcomes. The groups were similar in baseline characteristics. Twelve patients (57%) in the neutropenic diet and nine patients(43%) in the standard diet arm developed FN. Patients in ND-arm had significantly higher chance of getting neutropenic enterocolitis(NEC) (33.33% vs 4.76% p = 0.044). Mortality (14.29%vs 0%, p = 0.23) and requirement for admission (47.6%vs 19.05%, p = 0.06), was more in the ND-arm but statistically non-significant. There was no significant difference in antibiotic length. Adherence was similar in both groups (95% vs 98%). Neutropenic diet was not effective in reducing FN rate and was associated with higher rate of NEC when compared to the standard diet.